1990
DOI: 10.1088/0953-8984/2/28/004
|View full text |Cite
|
Sign up to set email alerts
|

TiK XANES in superconducting LiTi2O4and related compounds

Abstract: The mixed valence spinel Lil+xTi2-x04 (0 2 x 2 0.33) compounds are superconducting for x s 0.12 (T,,,, = 12.7 K) and present a metal or semiconductor-like transition for x = 0.2. In order to study the context of such interesting electronic properties, we performed Ti Kedge measurements in these compounds and in the related systems MgTi204 and TiO,.The evolution of the intensity, position and shape of the pre-edge and main edge features is reported. We show that these data do not support a one-electron descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
44
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 19 publications
10
44
0
Order By: Relevance
“…There are, in contrast, only a few reported studies of reduced valence in materials using Ti K-edge XANES. Of particular note are the works of Durmeyer et al [16] and Ra et al [17], who both studied Li 1+x Ti 2Àx O 4 (the former study included MgTi 2 O 4 and TiO 2 as reference compounds), and of Luca et al [18] who studied lithium intercalation compounds of anatase. In all cases, distinct trends in the form of the XANES signal with average titanium oxidation state were noted, and broadly similar results were seen in each study.…”
Section: Structure and Valence Of Nati 2 O 4 And Cati 2 Omentioning
confidence: 99%
“…There are, in contrast, only a few reported studies of reduced valence in materials using Ti K-edge XANES. Of particular note are the works of Durmeyer et al [16] and Ra et al [17], who both studied Li 1+x Ti 2Àx O 4 (the former study included MgTi 2 O 4 and TiO 2 as reference compounds), and of Luca et al [18] who studied lithium intercalation compounds of anatase. In all cases, distinct trends in the form of the XANES signal with average titanium oxidation state were noted, and broadly similar results were seen in each study.…”
Section: Structure and Valence Of Nati 2 O 4 And Cati 2 Omentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In the normal spinel-like structure (space group Fd3m) of LiTi 2 O 4 , the Li and Ti atoms are respectively at the positions of tetrahedral (8a) and octahedral (16d) sites.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is the rare oxide superconductor showing a sharp superconducting anomaly [2][3][4] in specific heat (C) in contrast to an unpronounced one in polycrystalline BaPb 1-x Bi x O 3 with a comparable T c~1 2 K. 12 The upper critical field H c2 (0) of LiTi 2 O 4 reported by several groups varied from 2 to 32.8 T. 3,7 Issues like whether the superconductivity in LiTi 2 O 4 can be well explained in the framework of BCS theory based upon the electron-phonon (e-ph) interactions and the role of the electron-electron (e-e) interactions have not been totally clearified. 9 Some theoretical predictions showed that LiTi 2 O 4 was a strong coupling BCS superconductor while the low temperature specific heat and magnetic susceptibility data implied for the conditions for weak coupling d-band superconductivity. [1][2][3][4]10 Furthermore, there has been a very recently revived debate on Anderson's resonating valance bond (RVB)-type ground state as the possible origin of superconductivity in cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the chemical and electronic properties of titanium oxides is of great interest in catalysis, geological sciences, and high-To superconductivity (Kung, 1989;Farges et al, 1997, Durmeyer et al, 1990. Core level spectroscopies are known to be a good tool for such purposes and have been exploited for various titanium oxides Wu et al, 1997 and references therein).…”
Section: Introductionmentioning
confidence: 99%